Etiologies of Optic Disc Edema in Tertiary Eye Care Centre in Nepal - Vaidya, Keepa; Bhandari, Sanjeeb; Gurung, Reeta (Nepalese Journal of Ophthalmology, 2018)
Introduction: Optic disc edema is a common clinical finding that can be caused by benign to vision and or life-threatening conditions. Objective: To investigate the etiologies of optic disc edema among patients presenting to Tilganga Institute of Ophthalmology, Kathmandu, Nepal. Materials and Methods: A retrospective chart review of patients with optic disc edema presenting to Neuro-ophthalmology department of Tilganga Institute of Ophthalmology from May 2012 to May 2014, was made. Results: 98 patients were diagnosed with disc edema. Females (64%) were frequently affected. It was noted more in the 21 – 50 age groups. Papilledema was the most frequent cause (35.7%) of disc edema followed by papillitis (28.6%), pseudopapilledma (18.4%) and ischemia (17.3%), respectively. Brain tumors (13%) were the most common etiology for papilledema. Conclusion: Papilledema along with other causes, are common etiologies for disc edema. A detailed history and careful evaluation are necessary as the treatment strategy highly depends on it’s underlying etiologies.